Human-derived acellular dermal matrix may be an alternative to autologous grafts in tympanic membrane reconstruction: systematic review and meta-analysis - Shan Xu; Xia Sun; Ning Yang; Aihui Yan (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Human-derived acellular dermal matrix (ADM) has been widely used as an effective alternative to autologous grafts in tympanoplasty. However, evidence of ADM as an alternative to autologous grafts in the repair of tympanic membrane (TM) perforation still lacks adequate empirical evidence. Objectives To determine the clinical safety and efficacy of human-derived ADM as TM graft material for tympanoplasty. Data sources The PubMed, EMBASE, Cochrane Library, EBSCO, Ovid, Scopus, and Web of Science databases and reference lists of the retrieved articles were searched, with no language restriction. Selection criteria All randomized controlled trials and retrospective cohort studies that compared the use of human-derived ADM and autologous grafts in tympanoplasty for TM perforation were included. Data collection and analysis Two review authors independently assessed risk of bias in the included studies and extracted data. The pooled results for continuous data were reported as a mean difference (MD) and 95% confidence intervals (CI). For dichotomous data, odds risk (OR) with 95% CI was used. ChI2 statistic and Galbraith plots were used to assess the heterogeneity. Publication bias was assessed with a funnel plot and Egger’s test. Main results Five retrospective cohort studies and four randomized controlled studies with a total of 610 participants were included in the meta-analysis. No significant differences in graft success (OR: 0.71 [0.39, 1.29], p = 0.26), air-bone gap (ABG) reduction (MD: − 0.59 [− 3.81, 1.19], p = 0.51), or complications (OR: 1.23 [0.07, 20.64], p = 0.89) were found between the ADM group and autologous graft group. The use of ADM significantly shortened tympanoplasty surgery time (MD: − 16.14 [− 21.22, − 11.07], p < 0.00001) and reduced postoperative pain (MD: − 2.57 [− 3.57, − 1.58], p < 0.00001) compared with the autologous graft group. Conclusion Human-derived ADM might be an effective alternative to autologous grafts for tympanoplasty. However, some of the studies that were included in the present meta-analysis had rather low methodological quality, and more adequately designed clinical trials should be performed in the future. Graphical abstract